The effect of perceived quality, perceived value, trust and marketing on purchase intention of organic products in Malaysia - Denis, Joachim Clement (2019)
The organic products industry is facing several challenges in Malaysia although the demand for such product in this country is growing. One of the challenges is that the supply of local organic product is not keeping up with the increased demand. The Jack of organic products in the market is one of the main barriers for these products to reach consumers. Hence, this study was conducted to investigate the effect of perceived quality, perceived value, and green trust on green purchase intention for an organic product in Malaysia. The study also considered marketing as a moderating variable. To meet the objective, a quantitative approach was employed involving a survey. A total of 532 questionnaires Were distributed conveniently to consumers who visited 38 organic food stores in Kuala Lumpur. Of the questionnaires distributed, 400 usable responses were obtained for data analysis, yielding a response rate of 87 percent. A structural equation modelling was applied to analyse the data using the PLS-SEM software. The study applies Theory Planned Behaviour as the underpinning theory. Theory Planned discussed about the underlying factors that influence consumer intention and behaviour. The results show significant relationships between perceived quality, perceived value, and trust on green purchase intention. Moreover, marketing was found to moderate the relationship between independent variables and green purchase intention. This study serves as an important foundation research on green food consumption patterns among Malaysia consumers and provides potential green food marketers in Malaysia with consumer insights into green awareness of organic food products and also in green trust element in organic food products.